Merdeka Belajar dan Kampus Merdeka: Kajian Filsafat Pendidikan Barat dan Timur Serta Realitasnya - Kardiyem; Mansyur Arsyad; Siti Mukoyimah (Jurnal Filsafat Indonesia, 2023)
Merdeka Belajar Kampus Merdeka (MBKM) is a new educational paradigm that seeks to make students capable of mastering various scientific fields, hard skills and soft skills in the world of work. MBKM is formulated based on the foundation of western and eastern educational philosophy. This study attempts to dialogue on good expectations, the goals of each school of philosophy (das sollen) which are correlated with the reality and gaps in the implementation of MBKM (das sein) in order to obtain a holistic picture. This research uses literature study with a philosophical hermeneutic approach as its research method. The research results show that the philosophy of MBKM has relevance to the educational foundations of humanism, constructivism and progressivism. Merdeka Learning has also been initiated long ago by various founding figures of the nation which were expressed explicitly and implicitly. The Certified Internship Student Program and the Teaching Campus are MBKM activities that facilitate students in developing teaching competencies outside of the classroom. The MBKM policy philosophically provides benefits for accelerating campus quality. Improving the quality of this campus can be done by adding facilities, improving the quality of human resources for educators, and developing a supportive curriculum, considering that there are still obstacles in its implementation